Cracking furnace tube coating material composition, cracking furnace tube coating and preparation method of cracking furnace tube coating

By adopting specific coating material compositions and preparation methods, the problem that the cracking furnace tube coating in the prior art is difficult to suppress free radicals and condensation coking under high temperature conditions, and the high dispersion and stability of the catalytically active elements are achieved, which significantly improves the coking inhibition performance and service life of the coating.

CN119592904AActive Publication Date: 2025-03-11PETROCHINA CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311167418.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing cracking furnace tube coating technology is difficult to effectively suppress radical coking and condensation coking under high temperature conditions, and the dispersion of catalytically active elements is low, resulting in uneven coking performance of the coating in different regions and short service life.

Method used

A coating material composition is used, including a first coating material and a second coating material. The first coating material consists of a catalytically active component, a complexing agent, a buffering agent and a dispersant, ensuring uniform dispersion of the catalytically active component through specific preparation steps. The second coating material is a liquid slurry or a mixture of solid particles, which contains inert protective components, fluxes, activators and fillers, enhancing the mechanical properties and stability of the coating through high-temperature thermal co-permeability technology.

Benefits of technology

The high dispersion and stability of catalytically active elements are achieved, and the coking inhibition performance and service life of the coating are significantly improved. Compared with traditional coatings, the coking inhibition rate is increased by 34% to 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592904A_ABST
    Figure CN119592904A_ABST
Patent Text Reader

Abstract

The invention provides a cracking furnace tube coating material composition, a cracking furnace tube coating and a preparation method of the cracking furnace tube coating. The coating material composition comprises a first coating material and a second coating material, the first coating material comprises the following components: a catalytic active component, a complexing agent, a buffering agent and a dispersing agent; the second coating material is liquid slurry or a solid particle mixture. The preparation method of the coating comprises the following steps: pretreating the surface of a base material; loading a first coating material on the surface of the pretreated base material, and forming a first coating after atmosphere stabilization treatment; and loading a second coating material on the surface of the first coating, and carrying out high-temperature thermal co-permeation to obtain the coating. According to the cracking furnace tube coating prepared from the coating material composition, catalytic active elements contained in the cracking furnace tube coating have high dispersity and are stable, and in the repeated use process, the migration phenomenon of the whole elements in the coating is few, and the element loss amount is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cracking furnace tube coating material composition and a cracking furnace tube coating and a preparation method thereof, and belongs to the technical field of olefin production in petrochemical industry. Background Art

[0002] Low-carbon olefins such as ethylene, propylene and butadiene are the most basic chemical raw materials in the petrochemical production process. The production capacity of ethylene has always been regarded as one of the signs of the development level of petrochemical industry. Steam cracking, as the main production method of ethylene at present, often requires thermal cracking of hydrocarbon raw materials at high temperatures of 750 to 875 ° C to produce low-carbon olefins. In order to meet the temperature conditions required for thermal cracking, the material of the steam cracking furnace tube is often selected from chromium-nickel alloys with excellent high-temperature resistance. However, under high temperature conditions, the iron and nickel atoms in the alloy will migrate to the outer surface of the substrate, and then enrich on the surface of the furnace tube and serve as catalytic active centers, accelerating the adhesion and deposition of coke on the cracking furnace tube. As coke continues to accumulate, on the one hand, it will cause the inner diameter of the furnace tube to shrink, the flow state of the raw gas in the tube to change, and the raw material processing capacity of the cracking furnace to decrease, which will have an adverse effect on the production capacity of ethylene; on the other hand, due to the large thermal resistance of the coke layer, the heat transfer efficiency of the cracking furnace tube will be reduced, and the energy consumption of the cracking furnace will increase. Generally speaking, industrial cracking furnaces often operate for 30 to 60 days before they need to be shut down for decoking. The decoking process often takes 48 hours or even longer before the cracking furnace tubes can be put back into production, which greatly limits the operating efficiency of the cracking furnace.

[0003] The cracking furnace tube coating technology is currently the most effective means to inhibit the coking of cracking furnaces. This technology mainly uses physical or chemical methods to prepare one or more layers of coatings on the inner surface of the cracking furnace tube. These coatings can not only play a shielding role on the catalytic coking active elements such as iron and nickel in the furnace tube substrate, but also reduce the corrosion effect of carburization on the cracking furnace tube during ethylene production. This technology can effectively inhibit the coking of the cracking furnace tube, greatly improve the operation cycle of the cracking furnace, and the reduction of coke generation on the inner surface of the furnace tube can further reduce the operating energy consumption of the cracking furnace.

[0004] At present, a variety of coating technologies have been developed in this field. Most of these coating technologies use inert coatings, which mainly play a shielding role on the iron and nickel elements in the furnace tube substrate. By preventing the formation of catalytic coking, the cracking furnace tube obtains good coking inhibition performance. However, most of these coating technologies are difficult to effectively inhibit the free radical coking and condensation coking generated during the cracking process. In order to obtain a better coking inhibition effect, researchers have proposed a new catalytic coating technology. This technology introduces catalytically active elements into the coating. These catalytically active elements can catalyze the free radical coking and condensation coking generated during the cracking process into gaseous gases such as carbon monoxide and carbon dioxide. The application of this coating technology can significantly reduce the amount of coke generated during the cracking process and further extend the operation cycle of the cracking furnace.

[0005] CN112708445A discloses a cracking device. The inner wall of the reactor of the device comprises a substrate, a metal layer, a first catalytic coating and a second catalytic coating. The first catalytic coating comprises a composition of MnxCr 3-x O4 manganese chromium oxygen complex, the second catalytic coating comprises a perovskite material composed of AMO3 and / or a perovskite material composed of (Na2O) y A triclinic nepheline-like substance of Na2[Al2Si2O8]; wherein A is an alkaline earth metal element, and M is selected from at least one of the elements of Group IIIB and Group IVB. The specific preparation steps of the coating are: (1) applying a metal powder mixture to the surface of a substrate of a cracking device, and curing the metal powder mixture under vacuum or inert atmosphere to form a metal layer on the surface of the substrate of the cracking device; (2) performing a heat treatment under low oxygen partial pressure atmosphere and high temperature conditions to form a first catalytic coating on the surface of the metal layer; (3) preparing a second catalytic coating on the first catalytic coating. The technology uses vapor deposition to prepare the metal layer, the first catalytic coating and the second catalytic coating. The prepared coating can reduce asphalt coking and free radical coking during the cracking process, and minimize the coking during the cracking process while keeping the olefin yield in the cracking product basically unchanged. However, the coating slurry used in this technology only uses metal salts and silica-alumina sol. During the slurry preparation process, the dispersion of metal ions in the system is difficult to ensure, which makes it impossible for the metal elements to be highly dispersed on the surface of the substrate during the subsequent slurry deposition process, so that the coating's ability to inhibit coking is limited to a certain extent. In addition, the coating prepared by this technology has a multi-layer structure, and the preparation process is relatively complicated. At the same time, this technical solution does not explore the overall stability and mechanical strength of the coating.

[0006] CN105885486A discloses a composite coating for inhibiting coking of furnace tubes and a preparation method thereof. The main components of the composite coating are BaCeO3 powder and silica sol. The preparation method of the coating formed by the composite coating is mainly to mix BaCeO3 powder, silica sol and water in a certain proportion in advance to form a slurry, and then apply it on the surface of the substrate, and form a coating for inhibiting coking by high-temperature calcination. The BaCeO3 powder in the coating inhibits coking and the solid particle size is 1 to 3 microns. Applied to a high-pressure thermal cracking device, the coating was subjected to a hydrocarbon fuel cracking experiment. The results showed that the furnace tube loaded with the coating had an inhibition rate of 56.5% on carbon deposition compared with a blank tube. Scanning electron microscopy showed that the coating was dense, the reaction tube was completely filled, the coating structure was more compact after the cracking experiment, and the overall morphology remained intact. Although the composite coating has good thermal conductivity and a high coking inhibition rate, the BaCeO3 powder prepared is micron-sized particles. Therefore, under high temperature conditions, the sintering phenomenon of the BaCeO3 particles in the coating will be more serious, which limits the coking inhibition effect of the coating to a certain extent.

[0007] CN102899067B discloses a cracking furnace tube. The cracking furnace tube includes a cracking furnace tube substrate and an inert coating attached to the inner wall surface of the cracking furnace tube substrate. The inert coating is a coating that can prevent coke from contacting the cracking furnace tube substrate and does not react with cracking raw materials and cracking products. The inert coating has a porous structure with an average pore radius of 0.5 to 15 nm. An active catalytic layer can also be attached to the surface of the inert coating. The inert coating contains silicon dioxide and / or a first metal oxide, and the metal in the first metal oxide is selected from one or more of aluminum, titanium, zirconium, manganese, chromium, lanthanum and magnesium. The active catalytic layer contains a second metal active component, and the metal in the second metal active component is selected from one or more of lithium, sodium, potassium, rubidium, calcium, strontium, barium, molybdenum, cobalt, nickel, iron, copper, cerium and praseodymium. The presence of the second metal active component enables the coating to have the function of catalyzing the reaction between coke and water vapor. The preparation method of the coating mainly includes the following steps: (1) using acetone and deionized water to ultrasonically clean the surface of the substrate; (2) preparing an inert coating slurry, and applying the slurry on the surface of the cracking furnace tube substrate by an impregnation method, and obtaining an inert coating after high-temperature calcination; (3) preparing an active element salt solution, using an impregnation method to load the active elements on the surface of the inert coating, and obtaining a cracking furnace tube loaded with the coating after high-temperature calcination. Although the coating prepared by this method has good anti-coking performance, since the active elements are loaded by the impregnation method, the active elements in the coating are significantly agglomerated with each other, and the dispersion of the active elements is not high. In addition, the subsequent high-temperature heat treatment process will further promote the mutual agglomeration between the elements, which makes the bonding force between the prepared catalytic active layer and the substrate weak, and the catalytic active elements cannot achieve the optimal catalytic coke conversion efficiency. On the other hand, this method does not study the stability of the prepared coating during repeated use.

[0008] CN103861662B discloses an anti-coking catalyst coating including an alumina barrier layer. The coating is a double-layer structure, including a catalyst layer and an alumina barrier layer, wherein the alumina barrier layer is prepared by pre-plating aluminum on the surface of a metal substrate and then subjecting the sample to high-temperature oxidation treatment. The main function of the alumina barrier layer is to inhibit the migration of catalytic coking elements inside the substrate to the outside and prevent the catalytic coking elements from being enriched on the coating surface. The catalyst layer is mainly composed of BaCe x Zr (1-x)The catalyst layer is mainly composed of O3 perovskite compounds, which are prepared by solid powder roasting. The main function of the catalyst layer is to catalyze the conversion of coke formed during the thermal cracking of heavy oil products, and convert the coke into gases such as CO or CO2. The anti-coking catalyst coating was subjected to a 200-hour fatigue test and a simulated cracking test. The results showed that the oxidant coating has good anti-coking performance. The anti-coking catalyst coating prepared by this method has good anti-coking performance and service life. However, since this method uses a solid powder roasting method to prepare the catalyst BaCe x Zr (1-x) O3 perovskite compounds, the perovskite particles prepared by the solid powder roasting method often have the problem of large particle size, which will affect the dispersion of the perovskite compounds in the catalyst coating, thereby limiting the catalytic activity of the catalyst coating. On the other hand, the loading of the catalyst layer is achieved by coating and roasting on the barrier layer. The bonding degree between the catalyst layer and the barrier layer is not high, and its impact on the service life of the coating needs further verification.

[0009] CN1546609A discloses a method for inhibiting and slowing down the coking of ethylene cracking furnace tubes. The method comprises the following steps: (1) using a mixed gas containing H2, N2 and trace amounts of NH3, H2O and O2 generated by the decomposition of liquid ammonia as a reducing gas to perform atmosphere treatment on the furnace tubes, and cooling the furnace tubes after the treatment; (2) mixing the prepared alloy powder and binder into a slurry, applying it to the surface of the furnace tubes after the atmosphere treatment, and placing it in a heating furnace for high-temperature diffusion treatment after drying and curing, cooling the furnace tubes after the treatment, removing the excess alloy powder coating on the surface of the furnace tubes, and preparing an alloy layer on the surface of the furnace tubes that can inhibit and slow down the coking. The alloy powder used in this technology is composed of aluminum, silicon, chromium, rare earth, catalyst and dispersant, and the catalyst is mainly ammonium chloride, sodium fluoride or cryolite. The thickness of the alloy layer prepared by this technology can reach more than 100 microns, and has a good coking inhibition effect. The binders used in this technology are mainly edible gelatin and polyvinyl alcohol. Although the coating has good coking inhibition performance and can reduce the amount of coking by up to 90%, the uneven mixing of elements in the slurry during the preparation process will lead to large differences in the distribution of elements in different coating areas, resulting in different coking inhibition performance in different areas of the coating and different coke deposition. At the same time, uneven heating of the coating surface will cause the coating structure to be easily damaged by thermal shock.

[0010] CN101724827A discloses a method for reducing coking of ethylene cracking furnace tubes and improving ethylene selectivity. The method comprises the following steps: (1) at the front end of the crossover temperature of the cracking reaction, a pre-treated solution containing ceramic elements and active component elements of a catalytic cracking catalyst is injected into the cracking furnace along with a carrier gas, and vapor deposition is performed at 500°C to 1000°C; wherein the ceramic elements are mainly Si, Al, Ca, B and other elements, and the catalytic active elements are mainly Ag, Cr, Cu, Ti and other elements, and the solvent of the pre-treated solution is an ethanol solution; (2) after vapor deposition, at 700°C to 1100°C, in a carrier gas atmosphere with an inert gas as the main component, the metal oxide deposited on the inner wall of the furnace tube is passivated to form a coating. The coking inhibition performance of the coating is tested using industrial naphtha as the cracking raw material. The results show that the coating can reduce the deposition of coke on the inner wall of the furnace tube by more than 80%, and can increase the volume percentage of ethylene in the product by 4.32%. The coating prepared by this method contains inert ceramic elements and catalytically active elements. The preparation steps are to load the two elements on the surface of the substrate in one step, and then obtain the coating through high-temperature passivation treatment. Although the coating is used in naphtha cracking reactions to significantly reduce the amount of coke generated, it can be seen from repeated test data that the amount of coke reduced by the coating prepared by this method during repeated use is reduced from 92.97% to 73.29%, and the coating's coking inhibition performance is significantly reduced, indicating that the catalytically active elements in the coating have migrated and lost, and the overall stability of the coating is poor.

[0011] In summary, if you want to make the cracking furnace tube coating have the function of catalytic coke gasification conversion, the existing technology mostly adopts the introduction of active elements such as Li, Na, K, Ru, Ce into the coating during the coating preparation process. The conventional introduction method mostly adopts the inert element component and the active element component to be dispersed in a solvent to form a slurry, and the above elements are loaded on the surface of the substrate by coating, vapor deposition, solid powder embedding and other methods. Through subsequent high-temperature heat treatment, the elements are combined with each other and co-infiltrated into the substrate alloy body phase to form the desired coating. Although the existing catalytic coating technology has a relatively good catalytic coking inhibition performance during the application process, the active elements in the slurry often agglomerate, making it difficult for the active elements to be highly dispersed on the surface of the substrate, and the coking inhibition performance of different regions of the prepared coating is not the same, so that in the actual use of the coating, different regions often have different thermal resistance coefficients due to different coke deposition amounts, which can easily cause overheating of local areas of the cracking furnace tube, and reduce the service life of the coating and the furnace tube. On the other hand, under the environment of high-temperature oxidation and continuous thermal shock, the bonding force between the coating elements and the substrate gradually weakens due to the combined effects of their own migration and high-temperature carburization, causing the coating to peel off from the substrate surface, destroying the coating structure and causing it to lose its protective function for the substrate. Summary of the invention

[0012] In order to solve the above technical problems, the purpose of the present invention is to provide a cracking furnace tube coating material composition, a cracking furnace tube coating and a preparation method thereof. The cracking furnace tube coating prepared by the coating material composition of the present invention has a higher dispersion of catalytically active elements contained therein, and the catalytically active elements are more stable, and the migration phenomenon of the overall elements in the coating is less.

[0013] In order to achieve the above-mentioned object, the first aspect of the present invention provides a cracking furnace tube coating material composition, which comprises: a first coating material and a second coating material;

[0014] Wherein, based on the total mass of the first coating material being 100%, it comprises the following components: 10-40% of a catalytically active component, 2-30% of a complexing agent, 5-20% of a buffer and 40-70% of a first dispersant; the catalytically active component comprises one or a combination of compounds of alkali metal elements, compounds of alkaline earth metal elements, compounds of rare earth metal elements and compounds of transition metal elements;

[0015] The second coating material is a liquid slurry or a solid particle mixture; based on the total mass of the liquid slurry as 100%, it includes the following components: 10-65% of an inert protective component, 0.1-3.0% of a flux, 1.0-5.0% of an activator, 20-80% of a filler and the remainder of a second dispersant; based on the total mass of the solid particle mixture as 100%, it includes the following components: 15-60% of an inert protective component, 0.1-2.5% of a flux, 1.0-6.0% of an activator and the remainder of a filler.

[0016] In the above-mentioned coating material composition, preferably, based on the total mass of the first coating material being 100%, it includes the following components: 10-29% catalytic active component, 5-15% complexing agent, 5-15% buffering agent and 40-70% first dispersant.

[0017] In the above-mentioned coating material composition, preferably, in the components of the first coating material, the alkali metal elements include one or a combination of Li, Na and K; the alkaline earth metal elements include one or a combination of Mg, Ca, Sr and Ba; the rare earth metal elements include one or a combination of La, Ce, Pr, Nd and Y; the transition metal elements include one or a combination of Co, Mn, Mo, Cu, Zn, V, Ti, Cr, W, Rh and Hf.

[0018] In the above-mentioned coating material composition, preferably, among the components of the first coating material, the chelating agent includes one or a combination of disodium nitrilotriacetate, disodium ethylenediaminetetraacetate, dithizone, 8-hydroxyquinoline, o-phenanthroline, potassium sodium tartrate and polyphosphate.

[0019] In the above-mentioned coating material composition, preferably, in the components of the first coating material, the buffer includes one or a combination of ammonium acetate, tris(hydroxymethyl)aminomethane and citrate.

[0020] In the above-mentioned coating material composition, preferably, among the components of the first coating material, the first dispersant includes one or a combination of deionized water, ethanol, ethylene glycol, acetone and chloroform.

[0021] In the above-mentioned coating material composition, preferably, the first coating material is prepared by at least the following steps: (a) mixing the catalytically active component, the buffer and a portion of the first dispersant, and stirring to form a mixed system; (b) mixing the complexing agent and another portion of the first dispersant to obtain a complexing agent solution; (c) under stirring conditions, adding dropwise the complexing agent solution obtained in step (b) to the mixed system obtained in step (a), and continuing to stir for a period of time after the addition is completed, to obtain the first coating material.

[0022] In the above-mentioned coating material composition, preferably, based on the total mass of the liquid slurry as 100%, it includes the following components: 15-60% inert protective component, 0.1-2.5% flux, 1.0-2.0% activator, 24-70% filler and the remainder of the second dispersant.

[0023] In the above coating material composition, preferably, based on the total mass of the solid particle mixture as 100%, it includes the following components: 24-58% inert protective component, 0.1-2.5% flux, 1.1-4.0% activator and the balance filler.

[0024] In the above-mentioned coating material composition, preferably, among the components of the second coating material, the inert protective component includes one or a combination of chromium, silicon and aluminum.

[0025] In the above-mentioned coating material composition, preferably, among the components of the second coating material, the flux includes one or a combination of chromium fluoride, sodium fluoride, zirconium chloride and potassium fluoride.

[0026] In the above-mentioned coating material composition, preferably, among the components of the second coating material, the activator includes one or a combination of ammonium chloride, ammonium fluoride and ammonium sulfate.

[0027] In the above coating material composition, preferably, among the components of the second coating material, the filler includes aluminum oxide or the like.

[0028] In the above-mentioned coating material composition, preferably, among the components of the second coating material, the second dispersant includes one or a combination of deionized water, ethanol, ethylene glycol, acetone and chloroform.

[0029] In the cracking furnace tube coating material composition of the present invention, the first coating material and the second coating material can be stored separately, and when preparing the coating, the first coating material and the second coating material are made to form a coating.

[0030] A second aspect of the present invention provides a method for preparing a cracking furnace tube coating, wherein the method uses the above-mentioned cracking furnace tube coating material composition to form a coating, and the method comprises the following steps:

[0031] (1) Pre-treating the substrate surface;

[0032] (2) loading a first coating material on the surface of the pretreated substrate, and then performing an atmosphere stabilization treatment to form a first coating;

[0033] (3) The second coating material is loaded on the surface of the first coating, and then high-temperature thermal infiltration is performed to obtain the cracking furnace tube coating.

[0034] In the above-mentioned preparation method, preferably, in step (1), the method of pre-treating the surface of the substrate comprises immersing the substrate in an inorganic acid solution.

[0035] In the above-mentioned preparation method, preferably, in step (2), the loading method of the first coating material includes one or a combination of liquid phase brushing, atomization spraying, physical vapor deposition, chemical vapor deposition and immersion.

[0036] In the above preparation method, preferably, in step (2), the loading amount of the first coating on the surface of the pretreated substrate is 74 to 370 g / m 2 .

[0037] In the above-mentioned preparation method, preferably, in step (2), the atmosphere stabilization treatment includes: using a mixture of nitrogen and hydrogen as a stabilizing treatment atmosphere, in the stabilizing treatment atmosphere, using programmed temperature increase to heat the substrate carrying the first coating material to a stabilizing treatment temperature, and after reaching the stabilizing treatment temperature, maintaining the temperature at a constant level for a period of time to complete the atmosphere stabilization treatment.

[0038] In the above-mentioned preparation method, preferably, in the atmosphere stabilization treatment in step (2), the stabilization treatment temperature is 500-750°C.

[0039] In the above-mentioned preparation method, preferably, in the atmosphere stabilization treatment in step (2), the constant temperature is maintained for 3 to 7 hours.

[0040] In the above preparation method, preferably, in step (3), the loading method of the second coating material includes liquid phase coating or solid powder embedding. It can be understood by those skilled in the art that when the second coating material is a liquid slurry, liquid phase coating is used for loading; when the second coating material is a solid particle mixture, solid powder embedding is used for loading.

[0041] In the above-mentioned preparation method, preferably, in step (3), the high-temperature thermal co-infiltration includes: performing high-temperature heat treatment on the substrate loaded with the second coating material.

[0042] In the above-mentioned preparation method, preferably, in the high-temperature thermal co-infiltration of step (3), the temperature of the high-temperature heat treatment is 850-1200° C., and the constant temperature is maintained for 4-9 hours.

[0043] In the above-mentioned preparation method, preferably, in step (3), the high-temperature thermal co-diffusion is carried out in a protective atmosphere, and the protective atmosphere includes nitrogen and / or argon, etc.

[0044] A third aspect of the present invention provides a cracking furnace tube coating, which is prepared by the above-mentioned method for preparing the cracking furnace tube coating.

[0045] According to a specific embodiment of the present invention, preferably, the thickness of the cracking furnace tube coating is 20 to 300 μm.

[0046] The technical solution of the present invention has at least the following beneficial effects:

[0047] The cracking furnace tube coating prepared from the coating material composition of the present invention is a ceramic coating. While the ceramic coating has the function of high-temperature protection of the substrate, it also has the function of catalytic gasification conversion of coke generated during hydrocarbon cracking. The ceramic coating has excellent mechanical properties, thermal corrosion resistance and sintering resistance. The catalytically active elements contained in the coating have a high degree of dispersion, so that the coating has an excellent inhibitory effect on coke during application. At the same time, the catalytically active elements contained in the coating are relatively stable. During repeated use, the overall element migration phenomenon in the coating is less and the element loss is low. Therefore, the ceramic coating can well inhibit the coking of the cracking furnace tube and increase the service life of the cracking furnace tube. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a cross-sectional SEM photograph of the ceramic coating prepared in Example 1.

[0049] Figure 2 This is the mapping energy spectrum of catalytically active elements on the surface of the ceramic coating prepared in Example 1.

[0050] Figure 3 This is the mapping energy spectrum of catalytically active elements on the surface of the ceramic coating prepared in Comparative Example 3.

[0051] Figure 4 This is the distribution diagram of catalytically active elements in the cross section of the ceramic coating prepared in Example 1.

[0052] Figure 5 The coking inhibition rate of the coatings prepared in Example 1, Example 6, Example 11 and Comparative Example 2 varies with the usage cycle. DETAILED DESCRIPTION

[0053] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0054] A first aspect of the present invention provides a cracking furnace tube coating material composition, which comprises: a first coating material and a second coating material;

[0055] Wherein, based on the total mass of the first coating material being 100%, it comprises the following components: 10-40% of a catalytically active component, 2-30% of a complexing agent, 5-20% of a buffer and 40-70% of a first dispersant; the catalytically active component comprises one or a combination of compounds of alkali metal elements, compounds of alkaline earth metal elements, compounds of rare earth metal elements and compounds of transition metal elements;

[0056] The second coating material is a liquid slurry or a solid particle mixture; based on the total mass of the liquid slurry as 100%, it includes the following components: 10-65% of an inert protective component, 0.1-3.0% (preferably 0.1-2.5%) of a flux, 1.0-5.0% of an activator, 20-80% of a filler and the remainder of a second dispersant; based on the total mass of the solid particle mixture as 100%, it includes the following components: 15-60% of an inert protective component, 0.1-2.5% of a flux, 1.0-6.0% of an activator and the remainder of a filler.

[0057] In some specific embodiments of the present invention, based on the total mass of the first coating material being 100%, it includes the following components: 10-29% catalytic active component, 5-15% complexing agent, 5-15% buffer and 40-70% first dispersant.

[0058] In some specific embodiments of the present invention, the alkali metal element includes one or more combinations of Li, Na and K, preferably Li and / or K; the alkaline earth metal element includes one or more combinations of Mg, Ca, Sr and Ba, preferably one or more combinations of Mg, Ca and Ba; the rare earth metal element includes one or more combinations of La, Ce, Pr, Nd and Y, preferably one or more combinations of La, Ce and Y; the transition metal element includes one or more combinations of Co, Mn, Mo, Cu, Zn, V, Ti, Cr, W, Rh and Hf, preferably one or more combinations of Ti, Cr and W.

[0059] In some specific embodiments of the present invention, the compounds of alkali metal elements, the compounds of alkaline earth metal elements, the compounds of rare earth metal elements and the compounds of transition metal elements may include salt compounds of these metal elements, and may also include organic compounds of these metal elements, preferably salt compounds of these metal elements, such as nitrates, chlorides, etc.

[0060] In some specific embodiments of the present invention, the complexing agent includes one or a combination of disodium nitrilotriacetate, disodium ethylenediaminetetraacetate, dithizone, 8-hydroxyquinoline, o-phenanthroline, potassium sodium tartrate and polyphosphate.

[0061] In some specific embodiments of the present invention, the buffer includes one or a combination of ammonium acetate, tris(hydroxymethyl)aminomethane, and citrate.

[0062] In some specific embodiments of the present invention, the first dispersant includes one or a combination of deionized water, ethanol, ethylene glycol, acetone, chloroform, etc. Preferably, the first dispersant includes deionized water and / or ethanol.

[0063] In some specific embodiments of the present invention, the pH value of the first coating material is 4-9.

[0064] In some specific embodiments of the present invention, the first coating material is prepared by at least the following steps: (a) mixing the catalytically active component, the buffer and a portion of the first dispersant, and stirring to form a mixed system; (b) mixing the complexing agent and another portion of the first dispersant to obtain a complexing agent solution; (c) adding the complexing agent solution obtained in step (b) to the mixed system obtained in step (a) under stirring conditions, and continuing to stir for a period of time after the addition is completed to obtain the first coating material.

[0065] In some specific embodiments of the present invention, the preparation step (a) of the first coating material is carried out under a constant temperature condition, and the constant temperature is 20-50°C, preferably 30-40°C.

[0066] In some specific embodiments of the present invention, in the preparation step (a) of the first coating material, the stirring speed is 200 to 600 rpm, preferably 200 to 450 rpm.

[0067] In some specific embodiments of the present invention, in the step (b) of preparing the first coating material, the concentration of the complexing agent solution is 0.01 to 1 mol / L, preferably 0.1 to 1 mol / L.

[0068] In some specific embodiments of the present invention, in the step (c) of preparing the first coating material, the dripping speed of the complexing agent solution is 0.1 to 5 mL / min, preferably 0.5 to 3 mL / min.

[0069] In some specific embodiments of the present invention, the preparation step (c) of the first coating material is carried out under a constant temperature condition, and the constant temperature is 20-50°C, preferably 30-40°C.

[0070] In some specific embodiments of the present invention, in the step (c) of preparing the first coating material, the stirring speed is 200-300 rpm.

[0071] In some specific embodiments of the present invention, in the step (c) of preparing the first coating material, the stirring time after the dropwise addition is completed is 20 to 75 minutes.

[0072] The catalytically active components used in the present invention include one of alkali metal elements, alkaline earth metal elements, rare earth metal elements, and transition metal elements, or a composite solid solution compound composed of several of these elements. Therefore, the coating provided by the present invention has the function of high temperature protection of the substrate and also has the function of catalytic gasification conversion of coke generated during hydrocarbon cracking.

[0073] In the coating preparation process of the existing catalytic coating technology, it is necessary to prepare the catalytic coating slurry in advance, and then form the required coating through coating and high-temperature heat treatment. In the slurry preparation process, the catalytic active components are directly injected. Therefore, whether the slurry is fully mixed and uniform will be an important factor affecting the dispersion of the catalytic active components in the coating. During the mixing process, the catalytic active components tend to agglomerate into large particles, which reduces the dispersion of the catalytic active components in the coating, and ultimately limits the anti-coking performance of the catalytic coating.

[0074] The present invention introduces a complexing agent into the first coating material, and adjusts the complexing effect of the complexing agent on the catalytically active components by controlling the pH value of the first coating material, the temperature of the preparation process, the stirring rate and other conditions, so that the agglomeration effect between the catalytically active components in the first coating material is effectively reduced.

[0075] In some specific embodiments of the present invention, based on the total mass of the liquid slurry being 100%, it includes the following components: 15-60% of an inert protective component, 0.1-2.5% of a flux, 1.0-2.0% of an activator, 24-70% of a filler and the remainder of a second dispersant.

[0076] In some specific embodiments of the present invention, based on the total mass of the solid particle mixture as 100%, it includes the following components: 24-58% inert protective component, 0.1-2.5% (preferably 0.1-2.0%) flux, 1.1-4.0% activator and the balance filler.

[0077] In some specific embodiments of the present invention, the inert protective component includes one or a combination of chromium, silicon, and aluminum.

[0078] In some specific embodiments of the present invention, the flux includes one or a combination of chromium fluoride, sodium fluoride, zirconium chloride and potassium fluoride.

[0079] In some specific embodiments of the present invention, the activator includes one or a combination of ammonium chloride, ammonium fluoride and ammonium sulfate.

[0080] In some specific embodiments of the present invention, the filler includes alumina and the like.

[0081] In some specific embodiments of the present invention, the particle sizes of the inert protective component and the filler are 100-350 meshes respectively.

[0082] In some specific embodiments of the present invention, the second dispersant includes one or a combination of deionized water, ethanol, ethylene glycol, acetone, chloroform, etc. Preferably, the second dispersant includes deionized water and / or ethanol.

[0083] In some specific embodiments of the present invention, the second coating material is prepared by stirring and mixing the components. Preferably, during the preparation of the second coating material, the components are stirred and mixed for 0.5 to 10 hours.

[0084] A second aspect of the present invention provides a method for preparing a cracking furnace tube coating, wherein the method uses the above-mentioned cracking furnace tube coating material composition to form a coating, and the method comprises the following steps:

[0085] (1) Pre-treating the substrate surface;

[0086] (2) loading a first coating material on the surface of the pretreated substrate, and then performing an atmosphere stabilization treatment to form a first coating;

[0087] (3) The second coating material is loaded on the surface of the first coating, and then high-temperature thermal infiltration is performed to obtain the cracking furnace tube coating.

[0088] In some specific embodiments of the present invention, the substrate is a high temperature resistant alloy steel, including GH series alloys, NS series alloys, or Incoloy series alloys, etc. Preferably, the GH series alloys may include Cr 20 Ni 35 Alloy, Cr 20 Ni 30 Alloy, Cr 15 Ni 60 Alloy, Cr 30 Ni 70 Alloy, Cr 20 Ni 80 Alloy, Cr 25 Ni 35 Alloy, or Cr 25 Ni 20 Alloys etc.

[0089] In some specific embodiments of the present invention, in step (1), the method of pretreating the surface of the substrate includes immersing the substrate in an inorganic acid solution.

[0090] In some specific embodiments of the present invention, in step (1), the inorganic acid includes one or a combination of hydrochloric acid, nitric acid, phosphoric acid and sulfuric acid, and preferably includes hydrochloric acid and / or nitric acid.

[0091] In some specific embodiments of the present invention, in step (1), the concentration of the inorganic acid solution is 0.01 mol / L to 0.1 mol / L.

[0092] In some specific embodiments of the present invention, in step (1), the soaking time is 10 min to 150 min, preferably 20 min to 120 min.

[0093] In some specific embodiments of the present invention, in step (1), the method of pre-treating the surface of the substrate further includes: washing and drying the substrate after being soaked in the inorganic acid solution. This process is to clean the inorganic acid remaining on the surface of the substrate on the one hand, and to keep the surface of the substrate dry on the other hand. The drying can be vacuum drying, the drying vacuum degree is 100-400 Pa, the drying temperature is 40-90°C (preferably 40-80°C), and the drying time is 0.1-5h (preferably 1-5h).

[0094] In some specific embodiments of the present invention, in step (2), the loading method of the first coating material includes one or a combination of liquid phase painting, atomization spraying, physical vapor deposition, chemical vapor deposition and immersion, preferably atomization spraying.

[0095] In some specific embodiments of the present invention, in step (2), the loading amount of the first coating on the surface of the pretreated substrate is 74 to 370 g / m 2 , preferably 74 to 300 g / m 2 .

[0096] In some specific embodiments of the present invention, in step (2), the atmosphere stabilization treatment includes: using a mixture of nitrogen and hydrogen as a stabilization treatment atmosphere, in the stabilization treatment atmosphere, using programmed temperature increase to heat the substrate carrying the first coating material to a stabilization treatment temperature, and after reaching the stabilization treatment temperature, maintaining the temperature at a constant level for a period of time to complete the atmosphere stabilization treatment.

[0097] In some specific embodiments of the present invention, in the atmosphere stabilization treatment of step (2), the volume concentration of hydrogen in the mixture of nitrogen and hydrogen is 10 to 40%, preferably 10 to 30%.

[0098] In some specific embodiments of the present invention, in the atmosphere stabilization treatment of step (2), the flow rate of the mixed gas of nitrogen and hydrogen is 10 to 100 mL / min, preferably 30 to 70 mL / min.

[0099] In some specific embodiments of the present invention, in the atmosphere stabilization treatment of step (2), the heating rate of the programmed temperature is 5 to 15° C. / min, preferably 5 to 10° C. / min.

[0100] In some specific embodiments of the present invention, in the atmosphere stabilization treatment in step (2), the stabilization treatment temperature is 500-750°C, preferably 500-650°C.

[0101] In some specific embodiments of the present invention, during the atmosphere stabilization treatment in step (2), the constant temperature is maintained for 3 to 7 hours.

[0102] In existing coating technologies, catalytically active components are often introduced by solvent coating. During the coating process, the catalytically active components will agglomerate with each other, resulting in the catalytic inhibition of coking performance of the prepared coating being limited. In addition, during long-term use, due to repeated high-temperature thermal shocks and high-temperature migration of elements, the service life of the existing coating is short, and the catalytically active elements are easily lost, resulting in the difficulty in maintaining the coating's inhibition of coking performance at a high level.

[0103] In the coating preparation method of the present invention, by acid-washing the substrate surface, defect sites can be constructed on the substrate surface, thereby strengthening the bonding effect between the first coating material and the substrate surface. After the first coating material of the present invention is loaded on the substrate surface, the catalytic active components can be evenly dispersed on the substrate surface, and combined with the atmosphere stabilization treatment, the catalytic active components will be reduced, and the complexing agent will be decomposed by the high temperature to facilitate the high-temperature thermal penetration of subsequent elements.

[0104] In some specific embodiments of the present invention, in step (3), the loading method of the second coating material includes liquid phase painting or solid powder embedding.

[0105] In some specific embodiments of the present invention, in step (3), the solid powder embedding specifically includes: embedding the substrate with the first coating in a container containing the second coating material, and the space between the substrate with the first coating and the container is filled with the second coating material to obtain a substrate loaded with the second coating material. The volume filling amount of the second coating material can be 90% to 100% of the total volume of the container. The position of the substrate with the first coating in the container can be located at the center of the container or at any position below it. The container is an inert container, preferably a high temperature resistant infiltration box.

[0106] In some specific embodiments of the present invention, in step (3), the high-temperature thermal infiltration includes: performing high-temperature heat treatment on the substrate loaded with the second coating material. Preferably, the high-temperature thermal infiltration specifically includes: using programmed temperature to heat the substrate loaded with the second coating material to 850-1200°C, and then maintaining the temperature for a period of time to complete the high-temperature thermal infiltration.

[0107] In some specific embodiments of the present invention, the high-temperature thermal co-diffusion in step (3) is carried out in a protective atmosphere, and the protective atmosphere includes nitrogen and / or argon, etc.

[0108] In some specific embodiments of the present invention, during the high-temperature thermal co-infiltration in step (3), the substrate loaded with the second coating material is heated to 850-1100°C, preferably 950-1100°C.

[0109] In some specific embodiments of the present invention, in the high-temperature thermal co-infiltration of step (3), the heating rate of the programmed temperature increase is 1 to 10° C. / min.

[0110] In some specific embodiments of the present invention, during the high-temperature thermal co-infiltration in step (3), the constant temperature is maintained for 4 to 9 hours.

[0111] In some specific embodiments of the present invention, step (3) further comprises: grinding and polishing after high-temperature thermal co-infiltration to obtain the cracking furnace tube coating.

[0112] In order to improve the stability of the catalytically active components under high temperature environment and inhibit the element migration and agglomeration of the catalytically active components under high temperature, the present invention further loads the second coating material on the surface of the first coating, so that the alumina filler in the second coating material fills the gaps between the catalytically active components, and through high-temperature thermal co-infiltration, the catalytically active components are fixed and blocked by the inert protective components under high temperature, and the agglomeration and migration phenomenon is effectively controlled. On the other hand, the introduction of the inert protective components will also enhance the overall mechanical properties of the coating of the present invention, so that the coating obtains stronger thermal corrosion resistance and sintering resistance. In the coking inhibition performance evaluation test, the coating of the present invention can increase the coking inhibition amount by 34% compared with the inert coating prepared by the traditional method; compared with the catalytic coating prepared by the traditional method, the coking inhibition amount can be increased by up to 23%; and after repeated coking inhibition evaluation tests, the coking inhibition performance of the coating of the present invention decreases less, and after use, the catalytically active components in the coating of the present invention can still maintain a high degree of dispersion.

[0113] A third aspect of the present invention provides a cracking furnace tube coating, which is prepared by the above-mentioned method for preparing the cracking furnace tube coating.

[0114] In some specific embodiments of the present invention, the thickness of the cracking furnace tube coating is 20 to 300 μm.

[0115] The cracking furnace tube coating provided by the present invention can be applied to the production of olefins, especially ethylene.

[0116] The existing cracking furnace tube coating technology uses physical or chemical methods to prepare one or more protective coatings on the inner surface of the cracking furnace tube. These coatings can not only play a shielding role on the catalytic coking active elements such as iron and nickel in the furnace tube substrate, but also reduce the corrosion effect of carburization on the cracking furnace tube during ethylene production. By further introducing catalytic active elements such as K, Ca or rare earth into the coating, the coating can obtain a catalytic conversion function for free radical coking and condensation coking. Although the existing coating technology has a relatively good shielding and catalytic conversion effect on catalytic coking, free radical coking and condensation coking, the dispersion of the catalytic active elements contained in these coating materials is often low, so that the inhibitory effect of the coating on coke in different areas during the application process is not the same, resulting in uneven local heating of the coating, resulting in a decrease in the overall mechanical properties of the coating and the service life of the cracking furnace tube. On the other hand, under the action of continuous thermal shock, the catalytic active elements contained in the existing coating technology will migrate and fall off, resulting in a decrease in the overall inhibitory effect of the coating.

[0117] The ethylene cracking furnace tube coating prepared from the coating material composition of the present invention is a ceramic coating. While the ceramic coating has the function of high-temperature protection of the substrate, it also has the function of catalytic gasification conversion of coke generated during hydrocarbon cracking. The ceramic coating has excellent mechanical properties, thermal corrosion resistance and sintering resistance. The catalytically active elements contained in the coating have a high degree of dispersion, so that the coating has an excellent inhibitory effect on coke during application. At the same time, the catalytically active elements contained in the coating are relatively stable. During repeated use, the overall element migration phenomenon in the coating is less and the element loss is low. Therefore, the ceramic coating can well inhibit the coking of the cracking furnace tube and increase the service life of the cracking furnace tube.

[0118] The technical scheme of the present invention is specifically described below through examples and comparative examples, but the present invention is not limited to these examples and can of course be implemented in various modifications within the scope of the gist of the present invention.

[0119] The raw materials used in the embodiments and comparative examples include:

[0120] Acetone: purchased from Sinopharm Reagent, AR (Shanghai test), ≥99.5%;

[0121] Disodium ethylenediaminetetraacetate: purchased from aladdin reagent, 98%;

[0122] Tris(hydroxymethyl)aminomethane: purchased from aladdin reagent, ACS, ≥99.8%;

[0123] Disodium nitrilotriacetate: purchased from aladdin reagent, >98.0%;

[0124] Cerium nitrate, potassium nitrate, calcium nitrate, and manganese chloride: purchased from Sinopharm Reagent, AR, 99.0%;

[0125] Potassium sodium tartrate: purchased from aladdin reagent, AR, 99.0%;

[0126] Sodium citrate: purchased from aladdin reagent, AR, 99.0%;

[0127] Ammonium acetate: purchased from Sinopharm Reagent, AR (Shanghai test), ≥98.0%;

[0128] Concentrated hydrochloric acid: purchased from Sinopharm Reagent, concentration ≥ 98%;

[0129] Chromium powder, silicon powder, and aluminum powder: purchased from Sinopharm Reagent, particle size 200 mesh;

[0130] Chromium fluoride and sodium fluoride: purchased from Sinopharm Reagent, AR;

[0131] Zirconium chloride and ammonium chloride: purchased from Sinopharm Reagent, AR (Shanghai test), ≥99.0%;

[0132] Alumina: purchased from Sinopharm Reagent, particle size is 200 mesh.

[0133] The analysis and testing methods used in the embodiments and comparative examples include:

[0134] 1. The surface morphology and elemental analysis of the coating material were characterized by a Hitachi SU8010 cold field emission scanning electron microscope with a scanning voltage of 25 kV. In order to better characterize the distribution state of the catalytically active elements in the coating bulk phase, the coating sample was first cut and the coating cross-section thickness was observed by electron microscopy. Based on the coating thickness, EDS single-point energy spectrum analysis was used to perform elemental analysis in the vertical direction from the outer surface of the coating to obtain a content change diagram of the catalytically active elements in the vertical direction of the coating.

[0135] 2. The coating coking inhibition performance test adopts a hanging plate evaluation device. The device hangs the coating sample in a tubular reactor, and simulates the steam cracking reaction conditions under high temperature conditions by passing water vapor and hydrocarbon raw gas into the tubular reactor. Using naphtha as the cracking raw gas, the coating hanging plate's coking inhibition performance was tested. The reaction conditions are: the mass ratio of naphtha to deionized water is 2:1, the naphtha flow rate is 8mL / min, and the deionized water flow rate is 3mL / min. After the two are mixed and preheated to 360°C, they are passed into the tubular reactor for cracking reaction. The cracking reaction temperature is maintained at 840°C, the reaction pressure is 30kPa, and the cracking reaction time is 5h. After the reaction is completed, the coating hanging plate is taken out, and the total weight W of the coating hanging plate after coking is weighed using an electronic balance 总重量 , after deducting the weight of the coating coupon before the evaluation test W0 through formula (1), the coking amount of the coating coupon W is obtained.焦炭 .

[0136] W 焦炭 =W 总重量 -W0 (1)

[0137] In order to better express the catalytic conversion effect of the coating on coke, the coking inhibition rate is used to illustrate the coking inhibition performance of the coating. The calculation formula of the coking inhibition rate is shown in formula (2):

[0138] S=(W 参比 -W 焦炭 ) / W 参比 ×100% (2)

[0139] Where S is the coking inhibition rate, W 焦炭 is the amount of coking on the coating coupon, W 参比 is the coking amount of the reference coupon (i.e., the coking amount of the coupon without coating).

[0140] 3. The coating stability performance test adopts a hanging evaluation device. The test is carried out by multiple cycle evaluation, the number of cycles is 6 times; the single evaluation time is 12h; the reaction conditions are: the mass ratio of naphtha to deionized water is 2.5:1, the naphtha flow rate is 11mL / min, the deionized water flow rate is 3mL / min, the two are mixed and preheated to 360℃ and then passed into the tubular reactor for cracking reaction. The cracking reaction temperature is maintained at 850℃ and the reaction pressure is 30kPa. After the reaction is completed, the coating hanging piece is taken out, and the coating coking inhibition rate Sn (n represents the number of test cycles, where n = 1, 2, 3, 4, 5, 6) is calculated using an electronic balance. After the calculation is completed, the coking coating hanging piece is placed in a muffle furnace and baked in an air atmosphere. The baking temperature is 900℃ and the baking time is 6h. After the furnace temperature drops to room temperature, the weight of the coating sample after removing the coke is taken out and re-measured. After the recording is completed, the coating sample is hung back into the evaluation device and the next evaluation cycle test is carried out under the same reaction conditions.

[0141] The composition of the raw material naphtha used in the above-mentioned coating coking inhibition performance test and coating stability performance test is shown in Table 1.

[0142] Table 1

[0143] Carbon number Normal alkanes / % Isoalkanes / % Olefins / % Cycloalkanes / % Aromatics / % total / % 3 0.4 0 0 0 0 0.4 4 3.15 0.77 0 0 0 3.92 5 6.55 4.17 0.01 0.64 0 11.37 6 7.15 6.78 0 4.78 0.77 19.48 7 6.66 5.64 0 7.16 1.48 20.94 8 4.62 6.61 0 5.47 2.64 19.34 9 3.16 4.63 0 3.95 1.7 13.44 10 2.02 3.86 0 1.19 0.61 7.68 11 0.51 2.43 0 0.18 0.02 3.14 12 0.23 0.06 0 0 0 0.29 total 34.45 34.95 0.01 23.37 7.22 100

[0144] Preparation of blank samples (i.e., samples without coating)

[0145] Take Cr 25 Ni 35The alloy was used as the substrate and first processed into several blank samples with a size of 30 mm × 15 mm × 5 mm. The samples were polished with sandpaper to remove the oxide layer on the surface of the samples, and then the surface of the samples was degreased and cleaned with acetone, and then ultrasonically cleaned and placed in a vacuum drying oven for drying. After drying, blank samples were obtained, which were recorded as KB-1.

[0146] Preparation of the first coating material A

[0147] Based on the total mass of the first coating material A being 100%, it is composed of the following components: 29% of cerium nitrate, 6% of disodium ethylenediaminetetraacetate, 10% of tris(hydroxymethyl)aminomethane and 55% of deionized water.

[0148] The preparation method of the first coating material A comprises the following steps:

[0149] (a) mixing cerium nitrate, tris(hydroxymethyl)aminomethane) and a portion of deionized water, and stirring at a constant temperature of 30° C. and a stirring speed of 400 rpm to form a mixed system;

[0150] (b) mixing disodium edetate with another portion of deionized water to obtain a disodium edetate solution having a concentration of 0.5 mol / L;

[0151] (c) adding the disodium ethylenediaminetetraacetic acid solution obtained in step (b) dropwise to the mixed system obtained in step (a) at a dropping speed of 3 mL / min; during the dropping process, the system is continuously stirred at a constant temperature of 40° C. and a stirring speed of 300 rpm; after the dropping is completed, stirring is continued for 60 min to obtain a first coating material A.

[0152] The pH value of the first coating material A is 8.

[0153] Preparation of the first coating material B

[0154] Based on the total mass of the first coating material B being 100%, it is composed of the following components: 19% of lanthanum nitrate, 5% of disodium nitrilotriacetate, 7% of sodium citrate and 69% of deionized water.

[0155] The preparation method of the first coating material B comprises the following steps:

[0156] (a) mixing lanthanum nitrate, sodium citrate and a portion of deionized water, and stirring at a constant temperature of 40° C. and a stirring speed of 400 rpm to form a mixed system;

[0157] (b) mixing disodium nitrilotriacetate with another portion of deionized water to obtain a disodium nitrilotriacetate solution having a concentration of 0.4 mol / L;

[0158] (c) adding the disodium nitrilotriacetate solution obtained in step (b) dropwise to the mixed system obtained in step (a) at a dropping speed of 2.5 mL / min; during the dropping process, the system is continuously stirred at a constant temperature of 40° C. and a stirring speed of 300 rpm; after the dropping is completed, stirring is continued for 60 min to obtain a first coating material B.

[0159] The pH value of the first coating material B is 8.

[0160] Preparation of the first coating material C

[0161] Based on the total mass of the first coating material C being 100%, it is composed of the following components: 17% of cerium nitrate, 6% of potassium nitrate, 5% of disodium nitrilotriacetate, 7% of tris(hydroxymethyl)aminomethane and 65% of deionized water.

[0162] The preparation method of the first coating material C comprises the following steps:

[0163] (a) mixing cerium nitrate, potassium nitrate, tris(hydroxymethyl)aminomethane) and a portion of deionized water, and stirring at a constant temperature of 40° C. and a stirring speed of 300 rpm to form a mixed system;

[0164] (b) mixing disodium nitrilotriacetate with another portion of deionized water to obtain a disodium nitrilotriacetate solution having a concentration of 0.4 mol / L;

[0165] (c) adding the disodium nitrilotriacetate solution obtained in step (b) dropwise to the mixed system obtained in step (a) at a dropping speed of 1.5 mL / min; during the dropping process, the system is continuously stirred at a constant temperature of 40° C. and a stirring speed of 300 rpm; after the dropping is completed, stirring is continued for 75 min to obtain a first coating material C.

[0166] The pH value of the first coating material C is 7.

[0167] Preparation of the first coating material D

[0168] Based on the total mass of the first coating material D being 100%, it is composed of the following components: 10% of cerium nitrate, 2% of manganese chloride, 10% of potassium sodium tartrate, 15% of ammonium acetate and 63% of deionized water.

[0169] The preparation method of the first coating material D comprises the following steps:

[0170] (a) mixing cerium nitrate, manganese chloride, ammonium acetate and a portion of deionized water, and stirring at a constant temperature of 20° C. and a stirring speed of 300 rpm to form a mixed system;

[0171] (b) mixing sodium potassium tartrate with another portion of deionized water to obtain a sodium potassium tartrate solution having a concentration of 1 mol / L;

[0172] (c) The potassium sodium tartrate solution obtained in step (b) is added dropwise to the mixed system obtained in step (a) at a dropping speed of 1.5 mL / min. During the dropping process, the system is continuously stirred at a constant temperature of 40° C. and a stirring speed of 300 rpm. After the dropping is completed, stirring is continued for 75 min to obtain a first coating material D.

[0173] The pH value of the first coating material D is 8.

[0174] Preparation of the first coating material E

[0175] Based on the total mass of the first coating material E being 100%, it is composed of the following components: 10% of cerium nitrate, 5% of calcium nitrate, 5% of disodium nitrilotriacetate, 10% of sodium citrate and 70% of deionized water.

[0176] The preparation method of the first coating material E comprises the following steps:

[0177] (a) mixing cerium nitrate, calcium nitrate, sodium citrate and a portion of deionized water, and stirring at a constant temperature of 40° C. and a stirring speed of 300 rpm to form a mixed system;

[0178] (b) mixing disodium nitrilotriacetate with another portion of deionized water to obtain a disodium nitrilotriacetate solution having a concentration of 0.4 mol / L;

[0179] (c) adding the disodium nitrilotriacetate solution obtained in step (b) dropwise to the mixed system obtained in step (a) at a dropping speed of 3 mL / min; during the dropping process, the system is continuously stirred at a constant temperature of 40° C. and a stirring speed of 300 rpm; after the dropping is completed, stirring is continued for 75 min to obtain a first coating material E.

[0180] The pH value of the first coating material E is 7.

[0181] Example 1

[0182] Take the KB-1 sample and perform acid pickling pretreatment on it. Use a dilute hydrochloric acid solution with a concentration of 0.1 mol / L. Take 300 mL of the dilute hydrochloric acid solution and place it in a glass beaker. Put the KB-1 sample into the dilute hydrochloric acid solution for soaking. After soaking for 30 minutes, take out the sample, wash the sample with water to clean the dilute hydrochloric acid solution remaining on the surface, and then put the sample into a vacuum drying oven. Set the drying temperature to 60°C and the vacuum degree to 400 Pa. After drying for 3 hours, take out the sample to obtain the pretreated sample.

[0183] The first coating material A was loaded on the surface of the pretreated sample by atomization spraying method, and the sample loaded with the first coating material A was subjected to atmosphere stabilization treatment using a mixture of nitrogen and hydrogen, the volume concentration of hydrogen in the mixture was 20%, and the specific conditions of the atmosphere stabilization treatment were: the mixture flow rate was set to 50 mL / min, the temperature was increased to 650°C at a heating rate of 5°C / min, and the temperature was maintained at 650°C for 3 hours to complete the atmosphere stabilization treatment and form the first coating A1. The sample was taken out and weighed, and the loading amount of the first coating A1 was 0.149 g.

[0184] The second coating material of this embodiment adopts a solid particle mixture, which is composed of the following components based on the total mass of the solid particle mixture as 100%: 25% chromium powder, 15% silicon powder, 1.3% chromium fluoride, 1.1% zirconium chloride, 1.5% ammonium chloride and the remainder of aluminum oxide. The preparation method of the second coating material is: put the weighed components into a mixer, mix for 10 hours, pour out the solid particle mixture, and obtain the second coating material.

[0185] The second coating material is loaded on the surface of the sample with the first coating A1 by a solid powder embedding method. The specific steps are as follows: embed the sample with the first coating A1 in an inert container containing the second coating material, the embedded sample is located at the center of the inert container, the volume filling amount of the second coating material is 100% of the inert container, the sample and the second coating material are compacted, and the inert container is sealed.

[0186] The sealed inert container is placed in a muffle furnace for high-temperature heat treatment. Nitrogen is used as the protective atmosphere. The temperature in the muffle furnace is increased from room temperature to 700°C at a heating rate of 10°C / min, and then increased from 700°C to 1050°C at a heating rate of 5°C / min. The constant temperature is maintained for 7 hours to complete the high-temperature thermal infiltration.

[0187] After cooling, the second coating material powder was removed, and the sample was ground and polished to obtain a sample with a ceramic coating, which was recorded as SS-1.

[0188] Example 2

[0189] The first coating material B was loaded on the surface of the pretreated sample provided in Example 1 by atomization spraying, and the sample loaded with the first coating material B was treated under the same atmosphere stabilization treatment conditions as in Example 1 to form a first coating B1. After weighing, the loading amount of the first coating B1 was 0.121 g.

[0190] This embodiment uses the same second coating material and loading method as in Embodiment 1. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 1, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-2.

[0191] Example 3

[0192] The first coating material C was loaded on the surface of the pretreated sample provided in Example 1 by atomization spraying, and the sample loaded with the first coating material C was treated under the same atmosphere stabilization treatment conditions as in Example 1 to form a first coating C1. After weighing, the loading amount of the first coating C1 was found to be 0.136 g.

[0193] This embodiment uses the same second coating material and loading method as in Embodiment 1. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 1, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-3.

[0194] Example 4

[0195] The first coating material D was loaded on the surface of the pretreated sample provided in Example 1 by atomization spraying, and the sample loaded with the first coating material D was treated under the same atmosphere stabilization treatment conditions as in Example 1 to form a first coating D1. After weighing, the loading amount of the first coating D1 was found to be 0.117 g.

[0196] This embodiment uses the same second coating material and loading method as in Embodiment 1. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 1, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-4.

[0197] Example 5

[0198] The first coating material E was loaded onto the surface of the pretreated sample provided in Example 1 by liquid phase brushing method, and the sample loaded with the first coating material E was treated under the same atmosphere stabilization treatment conditions as in Example 1 to form a first coating E1. After weighing, the loading amount of the first coating E1 was found to be 0.127 g.

[0199] This embodiment uses the same second coating material and loading method as in Embodiment 1. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 1, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-5.

[0200] Example 6

[0201] Take the KB-1 sample and perform acid pickling pretreatment on it. Use a dilute hydrochloric acid solution with a concentration of 0.05 mol / L. Take 300 mL of the dilute hydrochloric acid solution and place it in a glass beaker. Put the KB-1 sample into the dilute hydrochloric acid solution for soaking. After soaking for 45 minutes, take out the sample, wash the sample with water to clean the dilute hydrochloric acid solution remaining on the surface, and then put the sample into a vacuum drying oven. Set the drying temperature to 70°C and the vacuum degree to 400 Pa. After drying for 2 hours, take out the sample to obtain the pretreated sample.

[0202] The first coating material A was loaded on the surface of the pretreated sample by atomization spraying method, and the sample loaded with the first coating material A was subjected to atmosphere stabilization treatment using a mixture of nitrogen and hydrogen, the volume concentration of hydrogen in the mixture was 30%, and the specific conditions of the atmosphere stabilization treatment were: the mixed gas flow rate was set to 50 mL / min, the temperature was increased to 650°C at a heating rate of 5°C / min, and the temperature was maintained at 650°C for 5 hours to complete the atmosphere stabilization treatment and form the first coating A2. The sample was taken out and weighed, and the loading amount of the first coating A2 was 0.141 g.

[0203] The second coating material of this embodiment adopts a solid particle mixture, which is composed of the following components based on the total mass of the solid particle mixture as 100%: 25% chromium powder, 15% silicon powder, 2.1% sodium fluoride, 1.7% ammonium chloride and the remainder of aluminum oxide. The preparation method of the second coating material is: put the weighed components into a mixer, mix for 10 hours, pour out the solid particle mixture, and obtain the second coating material.

[0204] The second coating material is loaded on the surface of the sample with the first coating A2 by a solid powder embedding method. The specific steps are as follows: embed the sample with the first coating A2 in an inert container containing the second coating material, the embedded sample is located at the center of the inert container, the volume filling amount of the second coating material is 100% of the inert container, the sample and the second coating material are compacted, and the inert container is sealed.

[0205] The sealed inert container is placed in a muffle furnace for high-temperature heat treatment. Argon is used as the protective atmosphere. The temperature in the muffle furnace is increased from room temperature to 600°C at a heating rate of 10°C / min, and then increased from 600°C to 950°C at a heating rate of 5°C / min. The constant temperature is maintained for 5 hours to complete the high-temperature thermal infiltration.

[0206] After cooling, the second coating material powder was removed, and the sample was ground and polished to obtain a sample with a ceramic coating, which was recorded as SS-6.

[0207] Example 7

[0208] The first coating material B was loaded onto the surface of the pretreated sample provided in Example 6 by atomization spraying, and the sample loaded with the first coating material B was treated under the same atmosphere stabilization treatment conditions as in Example 6 to form a first coating B2. After weighing, the loading amount of the first coating B2 was 0.157 g.

[0209] This embodiment uses the same second coating material and loading method as in Embodiment 6. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 6, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-7.

[0210] Example 8

[0211] The first coating material C was loaded on the surface of the pretreated sample provided in Example 6 by atomization spraying, and the sample loaded with the first coating material C was treated under the same atmosphere stabilization treatment conditions as in Example 6 to form a first coating C2. After weighing, the loading amount of the first coating C2 was 0.144 g.

[0212] This embodiment uses the same second coating material and loading method as in Embodiment 6. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 6, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-8.

[0213] Example 9

[0214] The first coating material D was loaded onto the surface of the pretreated sample provided in Example 6 by liquid phase brushing, and the sample loaded with the first coating material D was treated under the same atmosphere stabilization treatment conditions as in Example 6 to form a first coating D2. After weighing, the loading amount of the first coating D2 was 0.126 g.

[0215] This embodiment uses the same second coating material and loading method as in Embodiment 6. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 6, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-9.

[0216] Example 10

[0217] The first coating material E was loaded onto the surface of the pretreated sample provided in Example 6 by atomization spraying, and the sample loaded with the first coating material E was treated under the same atmosphere stabilization treatment conditions as in Example 6 to form a first coating E2. After weighing, the loading amount of the first coating E2 was found to be 0.153 g.

[0218] This embodiment uses the same second coating material and loading method as in Embodiment 6. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 6, the sample is ground and polished to obtain a sample with a ceramic coating, which is denoted as SS-10.

[0219] Embodiment 11

[0220] Take the KB-1 sample and perform acid pickling pretreatment on it. Use a dilute hydrochloric acid solution with a concentration of 0.01 mol / L. Take 300 mL of the dilute hydrochloric acid solution and place it in a glass beaker. Put the KB-1 sample into the dilute hydrochloric acid solution for soaking. After soaking for 100 minutes, take out the sample, wash the sample with water to clean the dilute hydrochloric acid solution remaining on the surface, and then put the sample into a vacuum drying oven. Set the drying temperature to 50°C and the vacuum degree to 400 Pa. After drying for 5 hours, take out the sample to obtain the pretreated sample.

[0221] The first coating material A was loaded on the surface of the pretreated sample by atomization spraying method, and the sample loaded with the first coating material A was subjected to atmosphere stabilization treatment using a mixture of nitrogen and hydrogen, the volume concentration of hydrogen in the mixture was 10%, and the specific conditions of the atmosphere stabilization treatment were: the mixed gas flow rate was set to 70 mL / min, the temperature was increased to 650°C at a heating rate of 5°C / min, and the temperature was maintained at 650°C for 6 hours to complete the atmosphere stabilization treatment and form the first coating A3. The sample was taken out and weighed, and the loading amount of the first coating A3 was 0.122 g.

[0222] The second coating material of this embodiment adopts a solid particle mixture, which is composed of the following components based on the total mass of the solid particle mixture as 100%: 25% chromium powder, 15% silicon powder, 10% aluminum powder, 1.3% sodium fluoride, 1.7% ammonium chloride and the remainder of aluminum oxide. The preparation method of the second coating material is: put the weighed components into a mixer, mix for 10 hours, pour out the solid particle mixture, and obtain the second coating material.

[0223] The second coating material is loaded on the surface of the sample with the first coating A3 by a solid powder embedding method. The specific steps are as follows: embed the sample with the first coating A3 in an inert container containing the second coating material, the embedded sample is located at the center of the inert container, the volume filling amount of the second coating material is 100% of the inert container, the sample and the second coating material are compacted, and the inert container is sealed.

[0224] The sealed inert container is placed in a muffle furnace for high-temperature heat treatment. Nitrogen is used as the protective atmosphere. The temperature in the muffle furnace is increased from room temperature to 700°C at a heating rate of 10°C / min, and then increased from 700°C to 1100°C at a heating rate of 5°C / min. The constant temperature is maintained for 5 hours to complete the high-temperature thermal infiltration.

[0225] After cooling, the second coating material powder was removed, and the sample was ground and polished to obtain a sample with a ceramic coating, which was recorded as SS-11.

[0226] Example 12

[0227] The first coating material B was loaded onto the surface of the pretreated sample provided in Example 11 by atomization spraying, and the sample loaded with the first coating material B was treated under the same atmosphere stabilization treatment conditions as in Example 11 to form a first coating B3. After weighing, the loading amount of the first coating B3 was 0.111 g.

[0228] This embodiment uses the same second coating material and loading method as in Embodiment 11. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 11, the sample is ground and polished to obtain a sample with a ceramic coating, which is recorded as SS-12.

[0229] Embodiment 13

[0230] The first coating material C was loaded onto the surface of the pretreated sample provided in Example 11 by liquid phase brushing method, and the sample loaded with the first coating material C was treated under the same atmosphere stabilization treatment conditions as in Example 11 to form a first coating C3. After weighing, the loading amount of the first coating C3 was 0.133 g.

[0231] This embodiment uses the same second coating material and loading method as in Embodiment 11. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 11, the sample is ground and polished to obtain a sample with a ceramic coating, which is recorded as SS-13.

[0232] Embodiment 14

[0233] The first coating material D was loaded on the surface of the pretreated sample provided in Example 11 by atomization spraying, and the sample loaded with the first coating material D was treated under the same atmosphere stabilization treatment conditions as in Example 11 to form a first coating D3. After weighing, the loading amount of the first coating D3 was 0.130 g.

[0234] This embodiment uses the same second coating material and loading method as in Embodiment 11. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 11, the sample is ground and polished to obtain a sample with a ceramic coating, which is recorded as SS-14.

[0235] Embodiment 15

[0236] The first coating material E was loaded onto the surface of the pretreated sample provided in Example 11 by atomization spraying, and the sample loaded with the first coating material E was treated under the same atmosphere stabilization treatment conditions as in Example 11 to form a first coating E3. After weighing, the loading amount of the first coating E3 was found to be 0.109 g.

[0237] This embodiment uses the same second coating material and loading method as in Embodiment 11. After being treated under the same high-temperature thermal co-infiltration conditions as in Embodiment 11, the sample is ground and polished to obtain a sample with a ceramic coating, which is recorded as SS-15.

[0238] Example 16

[0239] The acid pretreatment, first coating material A loading and atmosphere stabilization treatment conditions for the KB-1 sample in this embodiment are the same as those in Example 1. The loading amount of the first coating A5 on the surface of the sample obtained through the above steps is 0.146 g.

[0240] The second coating material of this embodiment adopts liquid slurry, which is composed of the following components based on the total mass of the liquid slurry as 100%: 35% chromium powder, 17% silicon powder, 1.4% chromium fluoride, 1.1% zirconium chloride, 1.5% ammonium chloride, 24% aluminum oxide and 20% ethanol. The preparation method of the second coating material is: add the weighed components into a beaker, stir and mix for 40 minutes, and then pour out the liquid slurry to obtain the second coating material.

[0241] The second coating material is loaded on the surface of the sample with the first coating A5 by the liquid phase brushing method, and the sample coated with the second coating material is placed in a 60°C drying oven. After drying for 1 hour, the sample is taken out and placed in a muffle furnace for high-temperature heat treatment. Nitrogen is used as the protective atmosphere. The temperature in the muffle furnace is increased from room temperature to 700°C at a heating rate of 10°C / min, and then increased from 700°C to 1050°C at a heating rate of 5°C / min. The constant temperature is maintained for 7 hours to complete the high-temperature thermal co-infiltration.

[0242] After cooling, the sample was ground and polished to obtain a sample with a ceramic coating, which was recorded as SS-16.

[0243] Comparative Example 1

[0244] The inert coating material used in this comparative example is composed of the following components, based on the total mass of the inert coating material being 100%, 21% of chromium powder, 4% of silicon powder, 0.4% of chromium fluoride, 0.7% of zirconium chloride, 3.2% of ammonium chloride and 70.7% of aluminum oxide. The preparation method of the inert coating material is as follows: the weighed components are charged into a mixer, mixed for 10 hours, and then the solid particle mixture is poured out to obtain the inert coating material.

[0245] The inert coating material is loaded on the surface of the KB-1 sample by a solid powder embedding method. The specific steps are as follows: embed the KB-1 sample in an inert container containing the inert coating material, the embedded sample is located at the center of the inert container, the volume filling amount of the inert coating material is 100% of the inert container, the sample and the inert coating material are compacted, and the inert container is sealed.

[0246] The sealed inert container was placed in a muffle furnace for high-temperature heat treatment. Nitrogen was used as the protective atmosphere. The temperature in the muffle furnace was increased from room temperature to 700°C at a heating rate of 10°C / min, and then increased from 700°C to 950°C at a heating rate of 5°C / min. The constant temperature was maintained for 7 hours. After cooling, the inert coating material powder was removed, and the sample was ground and polished to obtain a sample with an inert coating, which was recorded as DB-1.

[0247] Comparative Example 2

[0248] Take a KB-1 sample and prepare a coating on it according to the technical solution disclosed in CN114540749A. The specific preparation steps are:

[0249] Take the KB-1 sample, embed it in an inert container containing the barrier coating penetrant, compact the sample and the barrier coating penetrant material, and seal the inert container. Wherein, based on the total mass of the barrier coating penetrant as 100%, it is composed of the following components: 21% chromium powder, 4% silicon powder, 0.4% chromium fluoride, 0.7% zirconium oxide, 3.2% ammonium chloride and 70.7% aluminum oxide. Put the sealed inert container into a muffle furnace for chemical heat treatment, and use a program temperature rise to raise the temperature in the muffle furnace from room temperature to 700°C at a heating rate of 10°C / min, and then raise the temperature from 700°C to 950°C at a heating rate of 5°C / min, and maintain the constant temperature for 7 hours. After cooling, remove the penetrant powder, grind and polish the sample to obtain a sample with a barrier coating.

[0250] The sample with the barrier coating is embedded in an inert container containing a coke clearing coating penetrant, the sample and the coke clearing coating penetrant are compacted, and the inert container is sealed. The coke clearing coating penetrant is composed of the following components based on the total mass of 100%: 16.5% chromium powder, 4% silicon powder, 0.2% chromium fluoride, 4.5% lanthanum oxide, 3.2% ammonium chloride and 71.6% aluminum oxide. The sealed inert container was placed in a muffle furnace for chemical heat treatment. The temperature in the muffle furnace was raised from room temperature to 700°C at a heating rate of 5°C / min, and then raised from 700°C to 850°C at a heating rate of 5°C / min. The constant temperature was maintained for 7 hours. After cooling, the penetrant powder was removed. The sample was polished and brushed with saturated calcium hydroxide solution twice, each time for 5 minutes. After drying, it was calcined in air at 600°C for 5 hours for stabilization treatment to obtain a sample with a self-cleaning coating, which was recorded as DB-2.

[0251] Comparative Example 3

[0252] Preparation of the first coating material F: Taking the total mass of the first coating material F as 100%, it is composed of the following components: 30% of cerium nitrate and 70% of anhydrous ethanol; the first coating material F is prepared by the following steps: mixing cerium nitrate and anhydrous ethanol, and continuously stirring for 60 minutes at a stirring speed of 400 rpm and a constant temperature of 40°C to obtain the first coating material F.

[0253] The first coating material F was applied to the surface of the KB-1 sample by liquid phase brushing method, and the sample coated with the first coating material F was subjected to atmosphere stabilization treatment using a mixture of nitrogen and hydrogen, the volume concentration of hydrogen in the mixture was 20%, and the specific conditions of the atmosphere stabilization treatment were: the mixture flow rate was set to 50 mL / min, the temperature was increased to 650°C at a heating rate of 5°C / min, and the temperature was maintained at 650°C for 3 hours to complete the atmosphere stabilization treatment and form the first coating F1. The sample was taken out and weighed, and the loading amount of the first coating F1 was 0.157 g.

[0254] The second coating material of this embodiment adopts a solid particle mixture, which is composed of the following components based on the total mass of the solid particle mixture as 100%: 25% chromium powder, 15% silicon powder, 1.3% chromium fluoride, 1.1% zirconium chloride, 1.5% ammonium chloride and the remainder of aluminum oxide. The preparation method of the second coating material is: put the weighed components into a mixer, mix for 10 hours, pour out the solid particle mixture, and obtain the second coating material.

[0255] The second coating material is loaded on the surface of the sample with the first coating F1 by a solid powder embedding method. The specific steps are as follows: embed the sample with the first coating F1 in an inert container containing the second coating material, the embedded sample is located at the center of the inert container, the volume filling amount of the second coating material is 100% of the inert container, the sample and the second coating material are compacted, and the inert container is sealed.

[0256] The sealed inert container is placed in a muffle furnace for high-temperature heat treatment. Nitrogen is used as the protective atmosphere. The temperature in the muffle furnace is increased from room temperature to 700°C at a heating rate of 10°C / min, and then increased from 700°C to 950°C at a heating rate of 5°C / min. The constant temperature is maintained for 7 hours to complete the high-temperature thermal infiltration.

[0257] After cooling, the second coating material powder was removed, and the sample was ground and polished to obtain a sample with a ceramic coating, which was recorded as DB-3.

[0258] Comparative Example 4

[0259] The KB-1 sample was pretreated using the same acid pretreatment conditions as in Example 1.

[0260] Preparation of the first coating material G: Taking the total mass of the first coating material G as 100%, it is composed of the following components: 45% of cerium nitrate and 55% of deionized water; the first coating material G is prepared by the following steps: mixing cerium nitrate and deionized water, and continuously stirring for 60 minutes at a stirring speed of 400 rpm and a constant temperature of 40°C to obtain the first coating material G.

[0261] The first coating material G was loaded on the surface of the pretreated sample by atomization spraying method, and the sample loaded with the first coating material G was subjected to atmosphere stabilization treatment using a mixture of nitrogen and hydrogen, the volume concentration of hydrogen in the mixture was 20%, and the specific conditions of the atmosphere stabilization treatment were: the mixed gas flow rate was set to 50 mL / min, the temperature was increased to 650°C at a heating rate of 5°C / min, and the temperature was maintained at 650°C for 3 hours to complete the atmosphere stabilization treatment and form the first coating G1. The sample was taken out and weighed, and the loading amount of the first coating G1 was 0.181 g.

[0262] The second coating material of this embodiment adopts a solid particle mixture, which is composed of the following components based on the total mass of the solid particle mixture as 100%: 25% chromium powder, 15% silicon powder, 1.3% chromium fluoride, 1.1% zirconium chloride, 1.5% ammonium chloride and the remainder of aluminum oxide. The preparation method of the second coating material is: put the weighed components into a mixer, mix for 10 hours, pour out the solid particle mixture, and obtain the second coating material.

[0263] The second coating material is loaded on the surface of the sample with the first coating G1 by a solid powder embedding method. The specific steps are as follows: embed the sample with the first coating G1 in an inert container containing the second coating material, the embedded sample is located at the center of the inert container, the volume filling amount of the second coating material is 100% of the inert container, the sample and the second coating material are compacted, and the inert container is sealed.

[0264] The sealed inert container is placed in a muffle furnace for high-temperature heat treatment. Nitrogen is used as the protective atmosphere. The temperature in the muffle furnace is increased from room temperature to 700°C at a heating rate of 10°C / min, and then increased from 700°C to 1050°C at a heating rate of 5°C / min. The constant temperature is maintained for 7 hours to complete the high-temperature thermal infiltration.

[0265] After cooling, the second coating material powder was removed, and the sample was ground and polished to obtain a sample with a ceramic coating, which was recorded as DB-4.

[0266] The analysis and test results of the above embodiments and comparative examples are described as follows.

[0267] 1. Surface morphology and elemental analysis of coating materials

[0268] pass Figure 1 , Figure 2 , Figure 3 , Figure 4 From the SEM photos of the coating and the EDS element characterization analysis results, it can be seen that the catalytically active components in the ceramic coating prepared by the present invention are uniformly dispersed on the surface of the ceramic coating, and the dispersion of the catalytically active components is relatively high. The ceramic coating is cut and the element distribution of the coating cross section is analyzed. From the analysis results, it can be seen that the catalytically active components can not only be uniformly distributed on the coating surface, but the catalytically active components in the coating body can still maintain a high dispersion, and the overall distribution of the catalytically active components is relatively uniform.

[0269] 2. Coating’s coking inhibition performance

[0270] The coking amounts and coking inhibition rates of the coatings prepared in Examples 1 to 16 and Comparative Examples 1 to 4 under the same coking inhibition performance evaluation conditions are shown in Table 2.

[0271] Table 2

[0272]

[0273]

[0274] It can be seen from the data in Table 2 that the ceramic coating prepared by the present invention has a good catalytic conversion function for coke. Taking the SS-1 data as an example, the coking amount of the ceramic coating of SS-1 is significantly reduced compared with the coking amount of the KB-1 blank sample, and the coking inhibition rate of SS-1 can reach up to 90.06%. Compared with the inert coating of DB-1, the coking inhibition rate of SS-1 is significantly improved. Compared with the existing DB-2 catalytic coating, the coking inhibition rate of SS-1 can be increased by up to 23%. Combined with the scanning electron microscopy characterization results, it can be seen that the catalytically active components in the ceramic coating prepared by the present invention can maintain a high degree of dispersion, the catalytically active components can give full play to their own catalytic effect, and the overall catalytic conversion efficiency of the ceramic coating for coke is relatively high, which ultimately enables the ceramic coating to have more excellent coking inhibition performance.

[0275] 3. Coating stability

[0276] By repeatedly using the coating and evaluating the coking inhibition performance, a coking inhibition rate of the coating prepared in Example 1, Example 6, Example 11 and Comparative Example 2 was obtained as a function of the use cycle period. Figure 5 As shown. Figure 5 It can be seen that the ceramic coating prepared by the present invention has basically the same anti-coking performance after repeated use. This shows that the catalytically active components in the ceramic coating of the present invention have high stability under high temperature environment, and the element migration and agglomeration effect under high temperature is weak. The inert protective component can fill the gaps between the catalytically active components through high-temperature thermal co-infiltration, so that the catalytically active components are fixed and blocked by the inert protective component under high temperature, and the agglomeration and migration phenomenon is effectively controlled.

[0277] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A cracking furnace tube coating material composition, comprising: a first coating material and a second coating material; Wherein, based on the total mass of the first coating material being 100%, it comprises the following components: 10-40% of a catalytically active component, 2-30% of a complexing agent, 5-20% of a buffer and 40-70% of a first dispersant; the catalytically active component comprises one or a combination of compounds of alkali metal elements, compounds of alkaline earth metal elements, compounds of rare earth metal elements and compounds of transition metal elements; The second coating material is a liquid slurry or a solid particle mixture; based on the total mass of the liquid slurry as 100%, it includes the following components: 10-65% of an inert protective component, 0.1-3.0% of a flux, 1.0-5.0% of an activator, 20-80% of a filler and the remainder of a second dispersant; based on the total mass of the solid particle mixture as 100%, it includes the following components: 15-60% of an inert protective component, 0.1-2.5% of a flux, 1.0-6.0% of an activator and the remainder of a filler.

2. The coating material composition according to claim 1, wherein Taking the total mass of the first coating material as 100%, The invention comprises the following components: 10-29% of catalytic active component, 5-15% of complexing agent, 5-15% of buffering agent and 40-70% of first dispersant.

3. The coating material composition according to claim 1, wherein: Among the components of the first coating material, the alkali metal elements include one or more combinations of Li, Na and K; the alkaline earth metal elements include one or more combinations of Mg, Ca, Sr and Ba; the rare earth metal elements include one or more combinations of La, Ce, Pr, Nd and Y; the transition metal elements include one or more combinations of Co, Mn, Mo, Cu, Zn, V, Ti, Cr, W, Rh and Hf.

4. The coating material composition according to claim 1, wherein In the components of the first coating material, the complexing agent includes one or a combination of disodium nitrilotriacetate, disodium ethylenediaminetetraacetate, dithizone, 8-hydroxyquinoline, o-phenanthroline, potassium sodium tartrate and polyphosphate.

5. The coating material composition according to claim 1, wherein: In the components of the first coating material, the buffer includes one or a combination of ammonium acetate, tris(hydroxymethyl)aminomethane and citrate.

6. The coating material composition according to claim 1, wherein: Among the components of the first coating material, the first dispersant includes one or a combination of deionized water, ethanol, ethylene glycol, acetone and chloroform.

7. The coating material composition according to claim 1, wherein: The first coating material is prepared by at least the following steps: (a) mixing the catalytically active component, the buffer and a portion of the first dispersant, and stirring to form a mixed system; (b) mixing the complexing agent and another portion of the first dispersant to obtain a complexing agent solution; (c) adding the complexing agent solution obtained in step (b) to the mixed system obtained in step (a) under stirring conditions, and continuing to stir for a period of time after the addition is completed to obtain the first coating material.

8. The coating material composition according to claim 1, wherein Taking the total mass of the liquid slurry as 100%, it includes the following components: 15-60% of inert protective component, 0.1-2.5% of flux, 1.0-2.0% of activator, 24-70% of filler and the balance of second dispersant.

9. The coating material composition according to claim 1, wherein: Taking the total mass of the solid particle mixture as 100%, it comprises the following components: Inert protective component 24-58%, flux 0.1-2.5%, activator 1.1-4.0% and filler balance.

10. The coating material composition according to claim 1, wherein: In the components of the second coating material, the inert protective component includes one or a combination of chromium, silicon and aluminum.

11. The coating material composition according to claim 1, wherein: In the components of the second coating material, the flux includes one or a combination of chromium fluoride, sodium fluoride, zirconium chloride and potassium fluoride.

12. The coating material composition according to claim 1, wherein: In the components of the second coating material, the activator includes one or a combination of ammonium chloride, ammonium fluoride and ammonium sulfate.

13. The coating material composition according to claim 1, wherein: In the composition of the second coating material, the filler includes aluminum oxide.

14. The coating material composition according to claim 1, wherein: Among the components of the second coating material, the second dispersant includes one or a combination of deionized water, ethanol, ethylene glycol, acetone and chloroform.

15. A method for preparing a cracking furnace tube coating, the method using the cracking furnace tube coating material composition according to any one of claims 1 to 14 to form a coating, the method comprising the following steps: (1) Pre-treating the substrate surface; (2) loading a first coating material on the surface of the pretreated substrate, and then performing an atmosphere stabilization treatment to form a first coating; (3) The second coating material is loaded on the surface of the first coating, and then high-temperature thermal infiltration is performed to obtain the cracking furnace tube coating.

16. The preparation method according to claim 15, wherein: In step (1), the method of pre-treating the surface of the substrate includes immersing the substrate in an inorganic acid solution.

17. The preparation method according to claim 15, wherein: In step (2), the first coating material is loaded in a manner including one or a combination of liquid phase painting, atomization spraying, physical vapor deposition, chemical vapor deposition and immersion; Preferably, in step (2), the loading amount of the first coating on the pretreated substrate surface is 74 to 370 g / m 2 ; Preferably, in step (2), the atmosphere stabilization treatment comprises: using a mixture of nitrogen and hydrogen as a stabilization treatment atmosphere, in the stabilization treatment atmosphere, heating the substrate carrying the first coating material to a stabilization treatment temperature by programmed temperature increase, and after reaching the stabilization treatment temperature, maintaining the temperature at a constant level for a period of time to complete the atmosphere stabilization treatment; More preferably, in the atmosphere stabilization treatment in step (2), the stabilization treatment temperature is 500 to 750°C; More preferably, in the atmosphere stabilization treatment in step (2), the constant temperature is maintained for 3 to 7 hours.

18. The preparation method according to claim 15, wherein: In step (3), the loading method of the second coating material includes liquid phase painting or solid powder embedding; Preferably, in step (3), the high-temperature thermal co-infiltration comprises: performing high-temperature heat treatment on the substrate loaded with the second coating material; More preferably, in the high temperature thermal infiltration of step (3), the temperature of the high temperature heat treatment is 850 to 1200° C., and the constant temperature is maintained for 4 to 9 hours; More preferably, in step (3), the high-temperature thermal co-diffusion is carried out in a protective atmosphere, and the protective atmosphere includes nitrogen and / or argon.

19. A cracking furnace tube coating, which is prepared by the method for preparing a cracking furnace tube coating according to any one of claims 15 to 18.

20. The cracking furnace tube coating according to claim 19, wherein: The thickness of the cracking furnace tube coating is 20 to 300 μm.

Citation Information

Patent Citations

  • Cracking furnace tube, and preparation method and application thereof

    CN102899067B

  • Anti-coking catalyst coating with alumina barrier layer

    CN103861662B

  • Method for reducing ethylene cracking furnace tube coking and improving ethylene selectivity

    CN101724827A

  • Cracking furnace tube, and preparation method and application thereof

    CN102899067A

  • Anti-coking catalyst coating having alumina barrier layer

    CN103861662A